Rompendo com [um] silêncio: uma crítica ao conhecimento produzido sobre silêncio organizacional - Marcos Junior de Moura Paula (2015)
The manufacturing capacity of human labor has been enhanced by and enhances the - cooperation over different times. According to Marx (2004), work is what distinguishes us from other animals because, unlike the latter, we devise before acting. The work mediates our exchange with nature ensuring the production and reproduction of our lives. For capital, labor is important just as the workforce as a factor of production, which performs the valorization of value. Through cooperation, the capital gets the labor force set to perform together what isolated labor force could not. Our purpose was to analyze the mechanisms used for the construction of a knowledge that enhances cooperation in the workplace to meet the interests of capital, i.e., the research on organizational silence. From an onto-practical analysis of the ideology, which analyzes the phenomenon by the social role it plays (VAISMAN, 2010), and with the aid of the operating modes of ideology (THOMPSON, 1995), we observed that the scholars legitimize the interests of capital, naturalize hetero-managed work relations, and hide that participation can lead to greater exploitation of workers due to increased productivity. Participation, which could mean enhancing worker control over the work process, means, rather, increased control by capitalists because workers earn more responsibility to correct processes or products without gaining the corresponding authority. Although scholars might have aimed to attack the Taylorism and Fordism assumptions that hinder the greater involvement of employees in the work process, aiming to get managers more open to criticism and negative feedbacks, they have not renounced to hold some reminiscences of these assumptions, as an indication of what a good worker is and their appropriate behavior in production settings.